Small Molecule Inhibitors of Interferon‐Induced JAK‐STAT Signalling. (15th June 2022) - Thoidingjam, Leishemba K.; Blouin, Cédric M.; Gaillet, Christine; Brion, Aurélien; Solier, Stéphanie; Niyomchon, Supaporn; El Marjou, Ahmed; Mouasni, Sara; Sepulveda, Fernando E.; de Saint Basile, Geneviève; Lamaze, Christophe; Rodriguez, Raphaël
Abstract: Interferons (IFN) are cytokines which, upon binding to cell surface receptors, trigger a series of downstream biochemical events including Janus Kinase (JAK) activation, phosphorylation of Signal Transducer and Activator of Transcription protein (STAT), translocation of pSTAT to the nucleus and transcriptional activation. Dysregulated IFN signalling has been linked to cancer progression and auto‐immune diseases. Here, we report the serendipitous discovery of a small molecule that blocks IFNγ activation of JAK‐STAT signalling. Further lead optimisation gave rise to a potent and more selective analogue that exerts its activity by a mechanism consistent with direct IFNγ targeting in vitro, which reduces bleeding in model of haemorrhagic colitis in vivo . This first‐in‐class small molecule also inhibits type I and III IFN‐induced STAT phosphorylation in vitro . Our work provides the basis for the development of pan‐IFN inhibitory drugs. Abstract : A small molecule that inhibits IFN‐induced JAK‐STAT signalling is reported. Chemical synthesis led to a series of more effective analogues that can selectively inhibit either IFN‐signalling or formin‐mediated actin assembly.